Litter Free Campaign (LIFC): a study on the employees' attitude and the roles of KKCH / Siti Noraisah Musneh and Halimatun Sohanah Sappari - Musneh, Siti Noraisah; Sappari, Halimatun Sohanah (2011)
Litter Free Campaign is a program that includes the Litter Free Event (LiFE). LiFE involved any event or program that prohibits people from littering during the event (Chua, 2000). While, Anti-Litter Bug is a program which does not focus on collecting the rubbish anymore, instead it is focusing on the litter bug reduction. This way is more effective compare to "Gotong Royong" which only collecting the rubbish and can lead to waste of time and energy, as people keep on littering, and local authority will pick up the rubbish later on. This is called as "throw- first-pick-up-later" syndrome.